Caracterização dos efeitos bioquímicos do óleo de bacuri (Platonia insignis) em camundongos machos - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The use of medicinal plants as a source of therapeutic products accompanies the history of humanity. The Platonia insignis is a native fruit species of the eastern Amazon, popularly known as Bacuri, the oil extracted from the seeds bacuri provides a chemical composition with high content of active substances with biochemical effects. This study aims to characterize the antioxidant and anti-inflammatory bacuri oil as possible preventive therapeutic alternative. Were utilized 15 male Swiss mices, divided into 3 groups. The oil bacuri at doses of 10 and 100 mg / kg and vehicle (olive oil - 10 ml / kg) were administered orally for 30 consecutive days. After 24 hours from the administration of the natural compound and vehicle proceeded to euthanizing the animals, and blood was collected by cardiac puncture and the plasma was used to perform biochemical analysis. Were evaluated biochemical parameters: Glucose, Total Cholesterol, LDL (Low Density Lipoprotein) cholesterol HDL (High Density Lipoprotein), Triglycerides, TGO (transaminase glutamic oxaloacetic), TGP (transaminase glutamic pyruvic transaminase), GGT (Gamma glutamyl transferase) urea, creatinine and Total Protein. Pre treatment with bacuri oil promoted beneficial effects on the parameters analyzed in this way this native fruit can be used as a more viable treatment option with regard to the minimization of drug and food interactions as well as in preventing disease.
Keywords: Platonia insignis; Fruto nativo; Estresse oxidativo; Efeito benéfico; Platonia insignis; Native fruit; Oxidative stress; Beneficial effect; CNPQ::CIENCIAS DA SAUDE